2017
DOI: 10.1080/15384101.2016.1249548
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of melanoma in vitro and in vivo via targeting with a Killer-Red-containing telomerase-dependent adenovirus

Abstract: Melanoma is a highly recalcitrant cancer and transformative therapy is necessary for the cure of this disease. We recently developed a telomerase-dependent adenovirus containing the fluorescent protein Killer-Red. In the present report, we first determined the efficacy of Killer-Red adenovirus combined with laser irradiation on human melanoma cell lines in vitro. Cell viability of human melanoma cells was reduced in a dose-dependent and irradiation-time-dependent manner. We used an intradermal xenografted mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Their studies have demonstrated that intratumor injection of TelomeKiller can inhibit the growth of non-small cell lung cancer and eliminate metastasis after the illumination of yellow-orange light (590 nm, 180 mW/cm 2 , 60 min) [ 62 ]. This recombinant vector is also efficient in eliminating human malignant melanoma after light stimulation (589 nm, 300 mW/cm 2 , 45 min) [ 63 ]. Moreover, a müller cells-specific adeno-associated virus vector expressed KillerRed in the vitreous of mice has been used to explore the changes in the structure and function of the retina after light stimulation (540–580 nm, 1000 lux, 60 min).…”
Section: Applications Of Killerred As An Endogenous Photosensitizermentioning
confidence: 99%
“…Their studies have demonstrated that intratumor injection of TelomeKiller can inhibit the growth of non-small cell lung cancer and eliminate metastasis after the illumination of yellow-orange light (590 nm, 180 mW/cm 2 , 60 min) [ 62 ]. This recombinant vector is also efficient in eliminating human malignant melanoma after light stimulation (589 nm, 300 mW/cm 2 , 45 min) [ 63 ]. Moreover, a müller cells-specific adeno-associated virus vector expressed KillerRed in the vitreous of mice has been used to explore the changes in the structure and function of the retina after light stimulation (540–580 nm, 1000 lux, 60 min).…”
Section: Applications Of Killerred As An Endogenous Photosensitizermentioning
confidence: 99%
“… 43 In contrast, PDT is a minimally invasive antitumor technique for inducing tumor‐specific cytotoxicity through the induction of photosensitizer‐mediated generation of ROS upon light irradiation. 44 , 45 For the application of hTERT promoter‐driven replicative viruses to PDT, we generated a telomerase‐specific replicative photodynamic viral agent known as TelomeKiller, which harbors the KillerRed expression cassette in the E3 region, enabling elimination of tumor cells through KillerRed‐mediated generation of ROS upon green‐light irradiation 46 , 47 (Figure 2 and Table 1 ). Thus, hTERT promoter‐driven viral vectors are useful tools for detecting and eradicating telomerase‐positive tumor cells.…”
Section: Tumor‐specific Promoter‐dependent Fluorescence Labelingmentioning
confidence: 99%
“…OBP-301 exhibits higher cancer selectivity than standard photosensitizers and only causes sustained tumor accumulation of the KillerRed protein in infected cancer cells [ 140 ]. In mice xenografts, OBP-301 with KillerRed and PDT had higher efficacy against colon cancer lymph node metastasis and orthotopic melanoma [ 141 ]. Similar approaches can be tested and further developed in the treatment of BC.…”
Section: Challenges and Prospectsmentioning
confidence: 99%